A discovery of witches ebook - Harkness, Deborah (All Souls, 2011)
Book one of the New York Times bestselling All Souls series, from the author of The Black Bird Oracle. Look for the hit series “A Discovery of Witches,” now streaming on Netflix “A wonderfully imaginative grown-up fantasy with all the magic of Harry Potter and Twilight ” ( People ). Deborah Harkness’s sparkling debut, A Discovery of Witches , has brought her into the spotlight and galvanized fans around the world. In this tale of passion and obsession, Diana Bishop, a young scholar and a descendant of witches, discovers a long-lost and enchanted alchemical manuscript, Ashmole 782 , deep in Oxford's Bodleian Library. Its reappearance summons a fantastical underworld, which she navigates with her leading man, vampire geneticist Matthew Clairmont. Harkness has created a universe to rival those of Anne Rice, Diana Gabaldon, and Elizabeth Kostova, and she adds a scholar's depth to this riveting tale of magic and suspense. The story continues in book two, Shadow of Night , book three, The Book of Life , and the fourth in the series, Time’s Convert .